Malnutrition among lactating women in sub-Saharan Africa: an analytic review of spatial distribution, burden and determinants - Girma, Bekahegn; Rahman, Azizur (Frontiers in Public Health, 2025)
Malnutrition, encompassing both underweight and obesity, poses a significant public health challenge for women worldwide, spanning across developed and developing nations. Sub-Saharan Africa (SSA) bears a notably high burden of underweight, despite recent years have seen a noticeable increase in obesity rates. Lactating women are especially vulnerable to malnutrition. This analytic review aimed to compile current knowledge on the spatial distribution, prevalence, and contributing factors of malnutrition among lactating mothers in Sub-Saharan Africa, highlighting research gaps. This review systematically searched previous primary studies and reports from databases including PubMed, MEDLINE, PsycINFO, Web of Science, HINARI, EMBASE, African Journal of Online (AJOL), Scopus and Google Scholar. Various significant findings were synthesized in textual descriptions, figures and tables. The prevalence of underweight among lactating women in sub-Saharan Africa exhibits considerable disparity, spanning from 5.6 to 54.8%. However, there was no comprehensive summarized evidence for this issue in the region. Additionally, our findings emphasize a deficiency in comprehending the geographic distribution and factors influencing malnutrition among lactating women in sub-Saharan Africa. The burden of overweight in SSA was 15.9% among reproductive women; this burden is going to be increased. However, there were no studies conducted among the most vulnerable women, lactating women. Similarly, despite the spatial distribution of obesity/overweight among reproductive omen in SSA was known, there were no evidences for lactating women who have high risk for malnutrition as pregnant women. Hence, conducting population-wide, representative, and comprehensive research utilizing Demographic Health Survey data from countries in sub-Saharan Africa is imperative to fully comprehend the extent of the problem and effectively address the burden of malnutrition in this vulnerable population. Additionally, identifying hotspot areas of malnutrition specifically among lactating women within sub-Saharan Africa through spatial distribution analysis is essential for allocating resources appropriately, addressing a critical concern in the region and helps to reduce morbidity and mortality.